The gender code of school science - Parker, Lesley Hannah (Curtin University, 1994)
This study focused on the relationship between gender and science.The position taken was that this relationship is in need of theoretically informed clarification, from a perspective which allows for the questioning of taken-for-granted assumptions about knowledge. Thus, the sociology of knowledge, a discipline concerned essentially with the ideological basis of knowledge, provided the theoretical underpinnings for the study.The study's overall purpose was to advance understanding of the gender/science relationship through the development and testing of a theory. Secondary school science, an area in which the problematic gender/science relationship is of particular concern and an area which suffers acutely from lack of theory in this regard, was selected as the specific focus.The problem central to the study concerned the manner in which the structure of curriculum and assessment in secondary schools appears to influence the relationship between gender and science. In addressing this problem, the study involved two major tasks. The first task was to develop a theory which reconceptualises and integrates three strands of previous research, namely, (i) theories about the sociology of knowledge and the school curriculum, drawing initially on the research of Bernstein (1971b), Young (1971b) and Broadfoot (1979); (ii) empirical research, conducted mainly by science educators, concerning the manner in which science curriculum and assessment policy and practice appear to interact with gender; and, (iii) theories developed from the postmodernist feminist critique of science. The second task was to test this theory through a socio-historical analysis of patterns of sex differences in participation and achievement in secondary school science in one Australian State, namely Western Australia.The theory of the gender code of school science is the major outcome of the integration of the intellectual and empirical activities described in this thesis. Essentially, it is a conceptual, sociological framework in which gender is a central category. It is shown, in this study, to have both descriptive and predictive power with respect to the gender/science relationship at secondary school level.